VvSVP1 negatively regulates gibberellin accumulation before the dormant bud break of grapevine triggered by hydrogen cyanamide - Jingyi Li; Pinqi Sun; Anni Chen; Jilong Xu; Peiyong Xin; Jinfang Chu; Chuanlin Zheng (Horticultural Plant Journal)
In grapevine, previous studies have suggested that, gibberellin (GA) inhibits bud break before dormancy release while enhanced after dormancy release; the capacity of GA accumulation shows a trend of first inhibition and then upregulation. However, the regulatory mechanism of GA metabolism genes expression is as yet unclear during the process of dormancy release. In this study, we further validated the effect of GA3 and hydrogen cyanamide (HC) on bud break of ‘Red Globe’ grape, confirmed inhibition and promotion effect, respectively. Restricted GA biosynthetic genes' expression and enhanced GA catabolic gene's expression were observed in the early stage after HC treatment, while opposite expression trend showed in the late stage. VvSVP1, a MADS-box transcription factor gene, was downregulated in the late stage, which might play an important role in regulating GA metabolism genes' expression. It was shown that, VvSVP1 could bind to the promoter regions of GA biosynthetic gene VvGA20ox6 and catabolic gene VvGA2ox3, negatively and positively regulated the corresponding genes' expression, respectively; the contents of GAs related to GA20ox were significantly reduced in the grape callus overexpressed VvSVP1, while the ratio of GAs related to GA2ox were significantly increased. Taken together, VvSVP1 can regulate the endogenous GAs level by manipulating the expression of GA metabolism genes before dormant bud break induced by HC. Our findings may provide some new theoretical insights for the study of bud dormancy regulation in the perennial woody fruit trees.